Disproportions of the Current Taxation System in Russia and Estimation of its Functional Capabilities to Provide the Income Basis of the Territories’ Budget (International Journal of Psychosocial Rehabilitation, 2020)
Background: The paper describes the main problems of the Russian taxation system and identifies the potential ways to solve them. Based on correlation-regression analysis, the authors show the interaction between the dynamics of tax revenues of the Russian consolidated budget and the level of tax load. In general, the analysis of the current disproportions in the Russian taxation system showed that only a complex solution of the existing problems would ensure its efficiency and improve its functional capabilities to provide the income basis of the territories’ budgets. Objective: to analyze the current Russian taxation system and to identify the key problems impeding the formation of a functional-efficient model of tax federalism. Methods: Methods such as correlation-regression, comparative and situational analysis, and expert estimations were used. Findings: The disproportions in the existing Russian taxation system were revealed, which impede the formation of a functional, efficient model of tax federalism (misbalance in allocation of taxes between authorities of different levels, changes of taxation legislation, irrational allocation of tax load, ineffective system of tax administration, and nonoptimal system of tax incentives); its functional capabilities to provide the income basis of the territories’ budgets were estimated. Conclusions: The research showed that a reverse linear correlation exists between the level of tax load and tax revenues of the Russian consolidated budget—the growth of tax load by 1% leads to a decrease in tax revenues of the consolidated budget, which testifies to the complex mechanism of forming the tax revenues of the consolidated budget in the Russian Federation.